A reassessment of archaeological human remains recovered from rock shelters in Cathkin Peak, South Africa. Issue 4 (2nd October 2021) - Meyer, Anja; Peyroteo-Stjerna, Rita; Jolly, Cecile; Schlebusch, Carina M.; Steyn, Maryna
ABSTRACT: Various skeletons from the uThukela region of the uKhahlamba-Drakensberg Mountains of South Africa were excavated from rock shelters there during the early part of the twentieth century, with limited accompanying data or analysis. This paper analyses and reports on nine such graves (eight of which contained human remains), excavated during 1931 near Cathkin Peak. The remains are currently housed in the Raymond A. Dart Archaeological Human Remains Collection, University of the Witwatersrand, Johannesburg. Most of the skeletons were radiocarbon-dated to between the fourteenth and mid-seventeenth centuries, but one is older and dates to between the seventh and ninth centuries AD. Remains recovered from the various shelters included those of both adults and children, males and females, indicating that these rock shelters were used for the burials of, and were possibly occupied by, a wide variety of individuals over a long period of time. Skeletal analyses revealed several signs of disease and trauma, attesting to some hardships living in this region of South Africa. Stable isotope analyses of carbon and nitrogen indicate a predominantly plant-based diet. Originally it was thought that these individuals' remains represented those of the historic amaZizi people, however, radiocarbon dates indicate that they are contemporaneous with the Moor Park phase of the Blackburn branch, which predates the amaZizi by several decades. Of interest is the fact that one individual predates the Moor Park phase. This is significant and sheds some light on the movement of people from KwaZulu-Natal into the interior. Future ancient DNA analysis will provide more information on the origin and genetic relationship of these individuals.